Penerapan Hukum Terhadap Pelaku Kekerasan Dalam Rumah Tangga (Studi Kasus di Pengadilann Negeri Padangsidimpuan) - Sutan Siregar (JUSTITIA : Jurnal Ilmu Hukum dan Humaniora, 2019)
The acts of violence in the family will have a negative impact on children and even families. Factors that cause domestic violence internally are 1) jealousy, 2) problems of children, 3) problems of courtesy, 4) problems of the past, 5) problems of misunderstanding, 6) problems of not cooking, 7) husbands want to win themselves. External factors are 1) financial problems, 2) parents' problems, 3) your problems. Penal sanctions, the application of penel sanctions are the application of criminal sanctions as regulated in Act Number 23 of 2004 concerning the Elimination of Domestic Violence. Non-penal sanctions, non-penal policies are entitled to: a) protection from family, police, prosecutors, courts, advocates, social institutions or other parties both temporarily and based on the stipulation of protection orders from the court; b) health services according to medical needs; c) handling specifically related to each inspection process in accordance with statutory provisions; and e) spiritual guidance services.Key words: Application of Law; Perpetrators;  Domestic Violence